(untitled) (Perner’s Contacts, 2014)
Paper provides insight into new trends in water transport, as maritime as inland waterway transport. Actual state of seaborne trade, word tonnage and port statistics. Significant part is also devoted to issue of container transport not only in Europe, but also in world perspective.